2014
DOI: 10.1007/s12032-014-0920-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD147 and Lewis y antigen in ovarian cancer and their relationship to drug resistance

Abstract: The purpose of this study was to investigate the relationship between the expression of CD147 and Lewis y antigen in epithelial ovarian carcinoma tissues and resistance to chemotherapeutic drugs, and its underlying clinical significance, and to analyze the correlation between the expression of CD147 and Lewis y antigen. Ninety-two ovarian cancer patients were divided into a chemotherapeutic-drug-resistant group (34 patients) and a drug-sensitive group (58 patients). Immunohistochemical assays were used to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…As a result, exploring the mechanism of drug resistance has become an important direction of current research. Lewis y antigen was reported to be positively correlated with CD147 in resistance to chemotherapeutic drugs in ovarian cancer by using immunohistochemical assays, and the results indicated that CD147 and Lewis y antigen expression were all independent risk factors for chemoresistance in ovarian cancer at the pathological stage [9]. Additionally, a study demonstrated the co-localization of annexin II and Lewis y antigen through the double-labeling immunofluorescence experiments, and that annexin II contained Lewis y antigen [10].…”
Section: Discussionmentioning
confidence: 92%
“…As a result, exploring the mechanism of drug resistance has become an important direction of current research. Lewis y antigen was reported to be positively correlated with CD147 in resistance to chemotherapeutic drugs in ovarian cancer by using immunohistochemical assays, and the results indicated that CD147 and Lewis y antigen expression were all independent risk factors for chemoresistance in ovarian cancer at the pathological stage [9]. Additionally, a study demonstrated the co-localization of annexin II and Lewis y antigen through the double-labeling immunofluorescence experiments, and that annexin II contained Lewis y antigen [10].…”
Section: Discussionmentioning
confidence: 92%
“…It mainly participates in cell-cell or cell-matrix interactions, stimulating adjacent fibroblasts to secrete a large numbers of matrix metalloproteinases (MMPs) and affects the invasion and metastasis of tumors. In addition, CD147 can suppress apoptosis and anoikis [21, 38], promote neovascularization, enhance resistance to several chemotherapeutic drugs [3, 17], promote the use of glycolysis in energy metabolism, and protect tumor cells from death [14, 20]. Another study has shown that CD147 is associated with autophagy [12], but did not identify a mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Expressed at high level, CD147 can promote the invasion and metastasis of tumor cells [35, 39], inhibit cell apoptosis and anoikis [21, 23], contribute to neo-vascularization and enhance resistance to several chemotherapeutic drugs [3, 17]. Gou X et al reported that CD147 involvement in the development of liver cancer is related to restrain autophagic cell death in liver cancer [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Известно, что EMMPRIN, выделенный из опухолевых клеток, паракринным способом стимулирует продукцию матричных металлопротеиназ соседними фибробластами [97]. Кроме того, он также стимулирует экспрессию фактора роста эндотелия сосудов и гиалуроновой кислоты, что приводит к ангиогенезу и множественной лекарственной устойчивости, которая, возможно, развивается путём активации фосфатидилинозитол-3-гидроксикиназы (PI3K) и митоген-активированных протеинкиназ (MAPK) [98]. Повышенная секреция EMMPRIN с сопутствующим увеличением секреции MMР-9 может обеспечивать более высокий метастатический потенциал, поскольку повышенная экспрессия этих двух белков выявлена при раке предстательной железы и плоскоклеточной карциноме шейки матки и является плохим прогностическим показателем для данных пациентов [99].…”
Section: роль тетраспанинов и протеаз экзосом в прогрессии злокачествunclassified